Teachers Perspectives on the Policy of Eliminating National Examinations and Its Impact on Junior High School Students in Sleman, Yogyakarta - Verrysaputro, Exwan Andriyan; Dian Bayu Firmansyah; Shafa Fikri Arifin; Andika Nicholas Saputra; Najwa Naila Khairunnisa; Afzhar Fitoro; Palupi Awalia Rahma; Fahima Nabila Al Firdaus; Umar Abdul Aziz (Unika Santu Paulus Ruteng, 2025)
Teachers feel uneasy with the decreasing motivation of students to learn. This has an impact on the decreasing academic quality at the elementary and secondary education levels. One of the causes is the elimination of national exams at the elementary and secondary levels. The elimination of national exams makes students reluctant to study seriously at school. The pros and cons of the policy of eliminating the implementation of national exams in Indonesia are the background to the study of this phenomenon. The purpose of this study is to describe the perspectives of teachers on the policy of eliminating national exams and their impact on junior high school students in Sleman, Yogyakarta. This study was conducted using a qualitative method. Data were collected using questionnaires, interviews, and literature studies. Data analysis in this study was carried out with the stages of data classification, data reduction, data presentation, and drawing conclusions. The results of this study indicate that 80% of teachers consider that the elimination of national exams has an impact on the lack of student learning motivation and results in a decrease in student enthusiasm in doing assignments. Thus, the results of this study are expected to be a consideration in evaluating the government's policy of eliminating national exams.